Designing Chibi Character Designs for a 2D Animated Video: “For You Who Love to Daydream” - Dewi Kirana Sekarayu; Diana Aqidatun Nisa; Aileena Solicitor Costa Rica El Chidtian (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Character design in 2D animation plays a crucial role in delivering narratives and building emotional connections with the audience. This study aims to design chibi-style characters for the 2D animated video “For You Who Love to Daydream”, which addresses the dangers of parasocial behavior among K-pop fans. The goal is to create characters that capture attention, foster emotional attachment, and enhance message effectiveness. The target audience consists of female K-pop fans aged 18–22 years. The method employed is descriptive qualitative, including observation, online visual data searches, questionnaires with the target audience, and interviews with chibi character design experts. The results show that the characters were designed to align with popular chibi art styles, integrate visual attributes reflecting K-pop fan identities, and effectively convey the video’s message while building emotional engagement. The final character design is expected to represent the target audience and serve as an educational medium that communicates emotional experiences related to the parasocial phenomenon.